Linking TVET with Industries in Bangladesh: Need for Supportive Policies and an Approach to TVET - Siddiky, Md. Roknuzzaman; Uh, Soo-Bong (Journal of Technical Education and Training, 2020)
While TVET is critical for development, there is a gap between skill development and employment, especially between TVET and industries in Bangladesh. As such, the study was intended to find out the supportive policies and an approach to TVET in order to link TVET with industries. The study was basically a qualitative study in which both primary and secondary data were used. Primary data were collected through semi-structured interviews with twelve purposively selected respondents working in various Government agencies and TVET institutions in Bangladesh. The study has indicated that the collaboration between TVET institutions and industries, and supportive public policy are necessary in order to link TVET with industries. Supportive public policy involves ensuring industries’ participation in designing curriculum and training, updating curriculum and training in response to market needs and changing technology, introducing dual system with strong focus on workplace learning, and public employment service, implementing National Skills Development Policy-2011 and National Skills Data System, and so on. The study has argued that the collaboration between TVET institutions and industries, and supportive public policy will create an enabling environment that would link TVET with industries in Bangladesh. Finally, the study has proposed a partnership-based approach to TVET where both the partners – TVET institution and industry – will work together and undertake joint initiatives based on mutual commitment and shared responsibility to promote formal and non-formal TVET in Bangladesh in line with labour market needs and technological changes.